Teaching and Learning in Higher Education - Liepa, Diāna; Špona, Ausma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of the article is development of structure of experience for the improvement of students’ learning experience. The research provides an explanation of models used in the process of language acquisition, it reflects the historical development of methodology, and it explores the student as a special subject of study work – an active person, performer of an activity. The process of foreign language acquisition is based on the attitude to the student as an active subject of this process. The process of language acquisition stimulates the students’ ability to use the foreign language in various situations of life. Research Methods Theoretical methods: analysis of scientific and methodological literature, modelling. Empirical research methods: methods of data acquisition – observation, experimenting, analysis. The research is based at the Riga Teacher Training and Educational Management Academy RTTEMA Pre-School and Primary School Teacher programmes.